Student character value in online learning during the Covid-19 pandemic - Soenaryo, Siti Fatimah; Susanti, Reni Dwi; Suwandayani, Beti Istanti (Technium Social Sciences Journal, 2021)
The purpose of this study was to find out how the student character values in learning activities carried out during the Pandemic. This research is quantitative descriptive. The data was taken using observation and questionnaires and then analyzed with quantitative methods and then described to see how the student’s character was seen from the indicators of honesty, hard work, discipline, communicative and responsible. The results of the study indicate that the value of student character during online learning is seen in the indicators of responsibility and discipline. While the indicators of honesty, hard work and communicativeness do not seem to get good results.